ANALYZING DE-ISLAMOPHOBIA FACTORS IN NEW YORK, USA - Taraki, Muhammad Dhiya; Pamuji, Muhammad Abdul Azis; Surwandono, Surwandono (Ulul Albab: Jurnal Studi Islam, 2024)
Recently, there has been a phenomenon of reducing the level of Islamophobia of the world community towards Muslims around the world, including Muslims in the United States. Allowing Muslims to carry out worship in public or open space, and the election of Muslim politicians in a government and congressmen are clear evidences to this phenomenon. This research aims to deeply analyze the de-islamophobia factors in New York City, The United States from 2017 to 2023. The phenomenon of Islamophobia, rising sharply since the 9/11 tragedy, has now begun to experience a significant decline, especially in the 2017-2023 period. A qualitative method was applied with literature studies. The data were taken from online books, online journals, and other relevant references such as online news. The study found various causes of the decline: socio-culture, demographic, and political events that contribute to the acceptance of Islam in the United States. Especially since Joe Biden was inaugurated as the U.S. President, the decline in Islamophobia is increasingly visible, particularly in the political fields.